Pretence Daily Life: Truco Game as Imaginary Mechanism to Escape Reality - Pinheiro, Alexandre Santos; Carrieri, Alexandre de Pádua (Organizações & Sociedade, 2014)
This paper looking for to talk about the Truco game like an element would allow the existence of the players because it would make their realities minimally bearable. We studied the symbolic dimensions of a Truco game that have happened along 23 years in a business organization. In this game “pawn shop floor” and “deputy CEO” have played. We used ethnography to catch the data. Participant observation and interviews helped us to catch the data. The players´ve meaning mean their work reality